Framing effects of incentives to promote child birth in Singapore - Neilson Hermantoso (2010)
In the context of Singapore government’s efforts to encourage higher birth rate in Singapore, this paper studies the effects of framing on people’s perception towards various kinds of monetary incentives, i.e. tax rebates and cash subsidies. This study was done through survey questionnaires in order to capture people’s perception towards the incentives. It was observed that the population perceives tax rebates differently from cash subsidies even when they are of the same economic value. Between the two, tax rebates are more favored as an incentive to promote higher birth rate in Singapore as compared to cash subsidies. This result was found among those with prior unfavorable attitude towards the policy of using monetary incentives to promote higher child birth. Among those with prior favorable attitude, the same result was also observed, even though they have smaller mean difference among their responses for tax rebates and cash subsidies. Loss aversion theory could be used to explain this phenomenon where people tend to minimize their losses.